'What a peaceful campaign!' The peace discourse as ZANU-PF's legitimacy seeking tool in the July 2013 election. Issue 3 (2nd October 2019) - Chibuwe, Albert
ABSTRACT: State-sponsored electoral violence targeting opposition political party supporters prior to and in the aftermath of elections remains a recurring phenomenon in post-independence Zimbabwe. Significant literature shows that the ruling Zimbabwe African National Union-Patriotic Front (ZANU-PF) party are the main engineers and beneficiaries of this culture of electoral violence. Much scholarly work has focused on the violent side of Zimbabwe's electoral contests. This paper, however, focuses on the peace discourse deployed by ZANU-PF during the July 2013 election in an effort to win legitimacy both locally and globally. The paper deploys sign theory and hegemony to interrogate how ZANU-PF sought to avert a legitimacy crisis post-2013 election. Methodologically, the paper subjects selected advertisement(s) to semiotic analysis. The paper's findings show that ZANU-PF's peace discourse was designed to create the illusion that its dominance is premised on consent. This was intended to subvert the dominant view that its longevity in power is due to coercion.